Militarism and Military Discourse in the Creation of a Nation: The Example of Turkish Modernization - Çatalbaş, Adem Üstün (My University, 2022)
Nations and nationalisms are, in the modern world, quite a fact. However, the biggest problem for a modern state is to create a nation from its citizens. In order to fulfill this task modern states have used every opportunity and tool. The military is one of these tools. As has its modern counterparts, the Turkish Republic has used its military to indoctrinate its citizens to create a nation. However, the usage of military has never been limited to time, or to the military itself. Both the military and militarist discourse, in modern Turkey, have involved and permeated almost every aspect of social life from the very beginning. This article is not the first attempt to examine the Turkish military and its effects in the country. Nevertheless, the militarist discourse have never been studied in all its complexity. This study intends to examine militarist discourse and indoctrination processes in Turkey from military, political, educational, and media points of view with the context of modernization.